2016
DOI: 10.3171/2016.5.focus16152
|View full text |Cite
|
Sign up to set email alerts
|

Application of morphometric analysis to patients with lung cancer metastasis to the spine: a clinical study

Abstract: OBJECTIVE Predicting the survival rate for patients with cancer is currently performed using the TNM Classification of Malignant Tumors (TNM). Identifying accurate prognostic markers of survival would allow better treatment stratification between more aggressive treatment strategies or palliation. This is especially relevant for patients with spinal metastases, who all have identical TNM staging and whose surgical decision-making is potentially complex. Analytical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 58 publications
1
9
1
Order By: Relevance
“…populations, confirms its association with poor clinical outcome [24,25,27,30,42,43]. Previous reports on nononcological spinal surgery populations have shown that morphometric analysis of the psoas could predict complications [44] and mortality [45].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…populations, confirms its association with poor clinical outcome [24,25,27,30,42,43]. Previous reports on nononcological spinal surgery populations have shown that morphometric analysis of the psoas could predict complications [44] and mortality [45].…”
Section: Discussionsupporting
confidence: 61%
“…Our results provide new, clinically relevant information to the existing literature regarding the role of sarcopenia on predicting early postoperative outcomes. Gakhar et al and Zhakaria et al have previously reported decreased survival with lower psoas size in patients with spinal metastasis [23,45]. In contrast to our study, Zakaria et al did not examine patients who underwent surgical intervention, but rather those treated with radiation therapy only.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The next best option is to use data from multiple studies using percentile based summative values. The literature currently uses a plethora of cohort-specific values, including using the lowest median, tertile, quartile, quintile, or standard deviation (19)(20)(21)23,24,27,28,(33)(34)(35)(36)(37)(38) in the study cohort. We validated our cohort's cutoff, by performing ROC curve analysis with regards to acute radiotoxicities which correlates to approximately a TPA of 500.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a recent study investigated the size of the psoas muscle as a prognostic factor in lung cancer patients with spinal metastasis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%